Temperature-driven structural identification of a steel girder bridge with an integral abutment. (15th January 2018) - Murphy, Brittany; Yarnold, Matthew
Highlights: Temperature-driven structural identification methodology is proposed. Model optimization is performed using measured vs. model thermal signatures. Numerical simulations characterize unknown boundary and continuity parameters. Thermal-induced damage of a steel girder integral abutment bridge is identified. Abstract: The Tennessee Department of Transportation (TDOT) visually detected recurring structural damage with one of their steel girder bridges in eastern Tennessee, USA. These issues prompted an investigation into the source of the damage. TDOT approached the structural research team in Tennessee Tech University's Civil and Environmental Engineering Department with what presented as damage related to thermal effects acting on the Anderson County Route 61 Bridge. In the presented study, temperature-driven structural identification is employed on the Route 61 Bridge to assess the structural damage and determine potential causes of such deterioration. An element-level, finite element model is created to provide insight regarding the bridge behavior. The bridge is field instrumented with monitoring equipment to quantify the bridge responses to daily thermal loads. The quantitative results are then used to calibrate the model and represent the bridge in its current condition. The root cause of the damage is identified through multiple numerical simulations and recommendations are provided for the long-term rehabilitation and preservation of the structure. Overall, the study contributes knowledge regarding the thermal behavior of steel girder integral abutment bridges including expansion/contraction movement, built-up strains/stresses, and potential damage produced by thermal loads. This study also provides illustration of an effective temperature-driven structural identification approach for evaluation of these types of structures.